1982
DOI: 10.1088/0029-5515/22/11/005
|View full text |Cite
|
Sign up to set email alerts
|

On the potentiality of the proton-boron fuel for inertially confined fusion

Abstract: Self-consistent time-dependent thermonuclear burn calculations were performed in order to investigate the potentiality of the proton-boron fuel for inertial confinement fusion. The results were compared with the approximate ones obtained by maximization of the ratio of thermonuclear energy to bremsstrahlung loss energy without consideration of the change in the ion and electron temperatures as well as of the change in the boron and proton concentrations caused by the burning process. It was found that for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Subsequently, the beryllium is divided into the two alpha particles of 2.74 MeV each. [1][2][3][4] The principle of the proton boron fusion therapy (PBFT) is based on this reaction as the radiation therapy technique. In the case of boron neutron capture therapy (BNCT), after the thermal neutron was captured by the labeled boron in the tumor region, an alpha particle is emitted from the capture reaction point.…”
mentioning
confidence: 99%
“…Subsequently, the beryllium is divided into the two alpha particles of 2.74 MeV each. [1][2][3][4] The principle of the proton boron fusion therapy (PBFT) is based on this reaction as the radiation therapy technique. In the case of boron neutron capture therapy (BNCT), after the thermal neutron was captured by the labeled boron in the tumor region, an alpha particle is emitted from the capture reaction point.…”
mentioning
confidence: 99%
“…This is certainly true in degenerate conditions (Gryzinski, 1958;Son and Fisch, 2004) and, away from degeneracy, e.g. for 𝑇 ≳ 𝑇 10 ⁄ when 𝑇 ≳ 150 keV and the boron-to-hydrogen ion concentration is lower than 50% (Levush and Cuperman, 1982).…”
Section: Introductionmentioning
confidence: 95%
“…The Spitzer-Sivukhin model (Spitzer, 1956;Sivukhin, 1966) has been used, in the form for a multicomponent (electrons and ion species), two-temperature H 11 B plasma detailed in Levush and Cuperman (1982). Earlier, this model had also been used by Moreau (1976Moreau ( , 1977 for slowdown calculations in high-density H 11 B plasma.…”
Section: Stopping Powers 𝑑𝐸 𝑑𝑥 ⁄ and 𝑑𝐸 𝑑𝑥 ⁄mentioning
confidence: 99%
“…To achieve a hot-ion mode in inertial confinement fusion using P-B-11, there have been proposals to generate a detonation wave [12][13][14][15]. Eliezer [13] showed that compressed fuel can be burned by an expanding ion fusion-burning wave preceded by an electron-conduction heat detonation wave.…”
Section: B Hot-ion Regime In Advanced Fuel Burningmentioning
confidence: 99%